Boryl Acrylaldehyde: An Elusive Member of the α-Boryl Aldehyde Class of Reagent - Trofimova, Alina; Brien, Chelsey; Trinchera, Piera; Tien, Chieh-Hung; Yudin, Andrei K. (Synlett, 2023)
We describe a synthetic route to boryl acrylaldehyde, an amphoteric molecule that features BMIDA and aldehyde functionalities attached to an sp2-carbon center. As the project unfolded, conventional protocols based on aldol condensation turned out to be unsuccessful. We eventually zeroed in on oxidative conditions that preserved the BMIDA group and delivered the desired aldehyde functionality. During our investigation, it became clear that boryl alcohol displays hemilabile N–B bonding, which differs dramatically from the previously described congeners with the sp3-carbon center connected to boron. We have attempted to understand the origins of this behavior using DFT calculations. Overall, boryl acrylaldehyde can be considered as an attractive entry point in synthetic methods. These studies are underway in our laboratory.
Keywords: boron; boryl aldehydes; amphoteric molecules; hemilability; boryl; oximes; boryl hydrazones